(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The auditor has a role in allocating joint costs in the gas industry, and the auditor’s procedures are considered as systematic critical examination, analysis and evaluation of everything related to costs in general and joint costs in the gas industry in particular, with the aim of controlling the joint costs of gas industry products, and knowing the share of the cost of each product from the total industry costs Gas products reflect the reality of the company’s performance by discovering weaknesses, defects and any errors, to ensure increased effectiveness and efficiency of the parties concerned with auditing them and imposing control and control over the company’s resources, as well as assisting the management in taking many decisions as well as reaching a proper measurement of the costs of each joint product without charging it with costs. Is a fact that did not benefit from it.